Motivación y desempeño laboral de los trabajadores de la Municipalidad Distrital de Jayanca, Provincia y Departamento de Lambayeque, 2022 - Guerra Puicón, Fiorella Lizbeth (2023)
This thesis was carried out with the purpose of analyzing the influence of motivation on the work performance of the workers of the District Municipality of Jayanca, Province and Department of Lambayeque, 2022. The type of applied research has been considered, based on a descriptive design, and the sample consisted of 48 workers belonging to the Jayanca District Municipality, with whom we worked applying the methods and techniques of quantitative research (statistical method and as technique to the virtual survey) and qualitative research (inductive - deductive method) and as a technique the structured interview. From the results obtained, it has been possible to determine that personal motivation and work motivation influence the attitude and work performance of the workers of the District Municipality of Jayanca, Consequently, it is important that the building institution knows its motivation plan and the work performance of its workers, which allows them to make an analysis of the results based on the present study. Of course, in the results it is determined that for there to be optimal job satisfaction, it is necessary that an adequate organizational climate exists in the organization. Finally, from the social work perspective, we believe that the company should promote training programs to develop a motivation plan, promote transformational leadership and work as a team to improve the level of service to users of the municipality. This thesis is subdivided into: Introduction: Problematic reality, background, theoretical bases and conceptual framework; Methodology; Results; Discussion; Conclusions; Recommendations; Bibliographic references and Annexes.